ADALIMUMAB THERAPY FOR REFRACTORY BIRDSHOT CHORIORETINOPATHY. Issue 11 (November 2019) - Huis in het Veld, Paulien I.; van Asten, Freekje; Kuijpers, Robert W.A.M.; Rothova, Aniki; de Jong, Eiko K.; Hoyng, Carel B.
Abstract : Purpose: To report the outcome of using adalimumab to treat birdshot chorioretinopathy. Methods: Retrospective case series of 19 patients (38 eyes) with HLA-A29–positive birdshot chorioretinopathy who received adalimumab treatment. Patients had been refractory to previous standard systemic immunomodulatory therapy. They received biweekly subcutaneous injections of 40 mg of adalimumab. Outcome measures were change in visual acuity, fluorescein angiography, and optical coherence tomography features, the concomitant use of immunosuppressive drugs, and the occurrence of adverse effects between 1 year before, at baseline, and after 1 year of adalimumab treatment. Results: Mean Snellen visual acuity at 1-year follow-up was 20/28, an improvement from 20/43 at the start of the treatment ( P = 0.011) and equal to the visual acuity 1 year before the treatment (20/29). Only 2 of the 9 patients who had complete fluorescein angiography and optical coherence tomography results after the 1 year of treatment were completely free of inflammation signs at the end of the follow-up. Half (53%) of 17 patients were receiving adalimumab monotherapy after 1 year of treatment, an increase from 21% at the start of treatment ( P = 0.047). Three of the 19 patients reported possible side effects; 2 discontinued treatment within 1 year. Conclusion: The results suggest that adalimumab is effective at improving visual acuity and at tapering concomitant immunomodulatory therapy, in patients with refractory birdshot chorioretinopathy. However, complete remission is rarely achieved. Abstract : Retrospective case series of 19 patients (38 eyes) with HLA-A29–positive birdshot chorioretinopathy who were treated with adalimumab. The results show that adalimumab is effective at improving visual acuity and at tapering concomitant immunomodulatory therapy, in patients with standard immunotherapy treatment–refractory birdshot chorioretinopathy. However, complete remission is rarely achieved.